From moderation to marginalization: language, power, and content governance on Indonesian social media platforms - Reza Pahlawan (Indonesian Journal of Language and Communication Studies, 2026)
Background: Content moderation increasingly governs linguistic visibility, public participation, and institutional authority across Indonesia’s multilingual social-media environment, where standardized harm categories may inadequately recognize contextual, regional, and identity-based expression. Objective: This study examines how regulatory language, platform policies, enforcement procedures, and civil-society critiques configure relationships among language, power, and marginalization in Indonesian content governance. Method: Using a qualitative corpus-assisted design, this study analyses 26 verified public documents from 2020–2026, integrating official regulations, platform standards, enforcement communications, civil-society assessments, and comparative governance materials across Indonesian public digital communication ecosystems, through critical policy discourse analysis, moderation-process mapping, and multimodal governance analysis. Results: Findings show that harm definition and contextual classification dominate governance discourse, while linguistic accessibility and culturally situated interpretation receive comparatively limited institutional attention. Enforcement documents prioritize automated detection, takedown, and compliance, whereas explanations, appeal mechanisms, and unequal consequences remain less systematically articulated. Implication: Civil-society and international materials consequently reposition transparency, proportionality, participation, localization, and independent review as necessary correctives to concentrated state-platform authority. Novelty: This study contributes an integrated account of moderation as a distributive governance system, demonstrating that marginalization may emerge not solely from content removal but from institutional asymmetries between classificatory power, visibility control, contextual competence, and users’ capacity to understand and contest decisions.